1999
DOI: 10.1093/ajcp/111.5.632
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Accuracy in Fine-Needle Aspiration of Soft Tissue and Bone Lesions: Influence of Clinical History and Experience

Abstract: A b s t r a c t Interpretation of soft tissue and bone lesions with fine-needle aspiration (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
47
0

Year Published

2000
2000
2011
2011

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 53 publications
(50 citation statements)
references
References 9 publications
3
47
0
Order By: Relevance
“…Most important, a needle biopsy should be used to establish the presence of malignancy and to determine whether a lesion is mesenchymal. From our data and that published within the literature, [3][4][5][6][7][8][9][10][11][12] FNA appears to perform many of the same functions as core needle biopsy.…”
Section: Resultssupporting
confidence: 53%
See 2 more Smart Citations
“…Most important, a needle biopsy should be used to establish the presence of malignancy and to determine whether a lesion is mesenchymal. From our data and that published within the literature, [3][4][5][6][7][8][9][10][11][12] FNA appears to perform many of the same functions as core needle biopsy.…”
Section: Resultssupporting
confidence: 53%
“…[3][4][5][6][7][8][9][10][11] Some of these studies have addressed the accuracy of FNA in histologic subtyping of mesenchymal tumors. [3][4][5][6][7][8][9][10][11] The success of subtyping tumors of the musculoskeletal system has varied among studies but generally has been between 50% and 70% accurate. 6 -10, 12 Some authors have demonstrated greater accuracy of subclassification for bone neoplasms, 12 whereas others have shown significantly less success with subclassification of soft tissue neoplasms.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Close interdisciplinary collaboration and constant vigilance by the surgeon can help prevent adverse patient outcomes attributable to incorrect FNAC. It was suggested that for cytopathologists of all levels of experience, knowledge of the patients' clinical background increased the proportion of correct diagnoses and accuracy of classification [17].…”
Section: Discussionmentioning
confidence: 99%
“…Successful FNAC is contingent on two main factors: an experienced cytopathologist and close collaboration between the orthopaedic oncologist and the pathologist [11,17]. For the past 8 years we have had such a situation, allowing for collection of a large database.…”
Section: Introductionmentioning
confidence: 99%